2014
DOI: 10.1007/s00005-014-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol on the Expression and DNA Methylation of Cytokine Genes in Diabetic Rat Aortas

Abstract: This paper studies the expression of proinflammatory cytokines such as IL-1β, IL-6, TNF-α, and IFN-γ and anti-inflammatory cytokines such as IL-10 in diabetic rat aortas, the effects of resveratrol on these cytokines, and the potential epigenetic mechanisms involved. The experiment was performed on rats divided into four groups: normal group (NC), normal interventional group (NB), diabetic group (DM), and diabetic interventional group (DB). The NB and DB groups were treated with resveratrol. After more than 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Briefly, RSV treatment reversed methylation‐mediated silencing of TSGs, BRCA1 , PTEN , APC , and RARbeta2 , in breast cancer . Furthermore, both RSV and PTS were shown to increase methylation at specific CpG loci located in pro‐inflammatory cytokines and fatty acid synthase gene, respectively, which resulted in gene suppression . In our recent genome‐wide study using methylation microarray technology, we further confirmed hyper‐ and hypomethylation upon treatment with stilbenoids and epigenetic silencing of oncogenic pathways in response to the compounds .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Briefly, RSV treatment reversed methylation‐mediated silencing of TSGs, BRCA1 , PTEN , APC , and RARbeta2 , in breast cancer . Furthermore, both RSV and PTS were shown to increase methylation at specific CpG loci located in pro‐inflammatory cytokines and fatty acid synthase gene, respectively, which resulted in gene suppression . In our recent genome‐wide study using methylation microarray technology, we further confirmed hyper‐ and hypomethylation upon treatment with stilbenoids and epigenetic silencing of oncogenic pathways in response to the compounds .…”
Section: Discussionsupporting
confidence: 53%
“…Stilbenoids were shown to exert anti‐cancer effects in cell lines and in vivo models, however, without a clear molecular mechanism demonstrated . There are a few reports by us and others on the involvement of epigenetics and specifically DNA methylation in the action of stilbenoids . Briefly, RSV treatment reversed methylation‐mediated silencing of TSGs, BRCA1 , PTEN , APC , and RARbeta2 , in breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…However, these increases were abolished in losartan-treated mice, accompanied with decreased blood pressure, mesangial hypertrophy and proteinuria [46]. Lou et al [47] aimed to investigate the effects of resveratrol (trans-3,5,40-trihydroxystilbene) on the expression of pro-inflammatory cytokines such as IL-1β, IL-6, TNF-α and IFN-γ in diabetic rat aortas and the potential epigenetic mechanisms involved. It showed that the expression levels of pro-inflammatory cytokines were significantly lower in the resveratrol-treated diabetic group.…”
Section: Epigenetic Reversibility and Potential Therapeutic Perspectivesmentioning
confidence: 99%
“…It showed that the expression levels of pro-inflammatory cytokines were significantly lower in the resveratrol-treated diabetic group. Furthermore, the untreated group showed reduced levels of DNA methylation at the specific cytosine phosphate guanosine sites of IL-1β, IL-6, TNF-α and IFN-γ and these levels were reversed by resveratrol [47]. Thus, although the studies were limited, they implicated that epigenetic modifications may be one of the protective mechanisms and it can be reversible, which may be used as a therapeutic tool targeting diabetic vascular complications.…”
Section: Epigenetic Reversibility and Potential Therapeutic Perspectivesmentioning
confidence: 99%
“…RSV also demonstrated inhibitory effect on NF- κ B activity and ameliorated the elevated levels of inflammatory proteins, TNF- α (tumour necrosis factor- α ), interleukin- (IL-) 6, and COX-2 (cyclooxygenase 2), thus contributing to reduction in neuroinflammation and protection against functional and behavioural deficits in diabetic neuropathy [106]. The anti-inflammatory property of RSV has been confirmed in diabetic animals by the downregulation of proinflammatory genes and proteins like TNF- α , IL-1 β , IL-6, IL-4, IL-17, COX-2 intercellular adhesion molecule 1 (ICAM), and vascular cell adhesion protein 1 (VCAM1) [14, 19, 22, 24, 107, 108] which are downstream targets of NF- κ B. In addition, RSV significantly decreased the activation and recruitment of macrophages thereby retarding the inflammation process in diabetic rats [22, 109].…”
Section: Mechanisms Of Protection Of Resveratrol In Diabetes Mellimentioning
confidence: 99%